The clinical spectrum of IgM monoclonal gammopathy: A single center retrospective study of 377 patients. (July 2016) - Cao, Xin-xin; Meng, Qi; Mao, Yue-ying; Su, Wei; Zhen, Jun-feng; Shen, Kai-ni; Zhang, Chun-lan; Huang, Xu-fei; Duan, Ming-hui; Zhang, Wei; Zhu, Tie-nan; Cai, Hua-cong; et al.
Highlights: IgM monoclonal gammopathy contains a broad spectrum of diseases. Levels of serum IgM can be used as one parameter for differential diagnosis. Type of light chain can be used to help differential diagnosis among IgM monoclonal gammopathy. The relationship between MGUS and some autoimmune diseases requires further investigation. Abstract: Objectives: We retrospectively evaluated the clinical features, serum levels of IgM, and prevalence of IgM related diseases in patients with serum immunofixation electrophoresis (sIFE) confirmed IgM monoclonal gammopathy at our center. Methods: We included patients with sIFE confirmed IgM monoclonal gammopathy between January 2008 and December 2014 in this retrospective study. We evaluated clinical data, sIFE, serum IgM levels, and diagnosis. Results: In total, 7107 patients had sIFE confirmed monoclonal gammopathy, with 377 (5.3%) patients having the IgM type. The median age was 62 years (range, 19–105 years). The median level of serum IgM is 8.3 g/L (range, 0.24–150 g/L). The diagnosis included monoclonal gammopathy of undetermined significance (MGUS, 157 patients, 41.6%), Waldenstrom macroglobulinemia (WM, 105 patients, 27.9%), B cell non-Hodgkin's lymphoma (69 patients, 18.3%), primary cold agglutinin disease (pCAD, 16 patients, 4.2%), primary amyloidosis (14 patients, 3.7%), cryoglobulinaemia (six patients, 1.6%), IgM MGUS associated neuropathy (five patients, 1.3%), multiple myeloma (three patients, 0.8%), and POEMS syndrome (two patients, 0.5%). Levels of serum IgM > 15.5 g/L were 80.6% sensitive and 89.2% specific for the diagnosis of WM. Kappa type light chain indicated the diagnosis of WM, pCAD, IgM MGUS associated neuropathy and cryoglobulinaemia, while lambda type light chain indicated POEMS and amyloidosis. There were 41/157 (26.1%) MGUS patients diagnosed with complications due to IgM-unrelated autoimmune diseases. Conclusion: IgM monoclonal gammopathy contains a broad spectrum of diseases. Levels of serum IgM and the type of light chain can be used to help with differential diagnosis. The association between MGUS and some autoimmune diseases requires further investigation.